Pengaruh Efektivitas Komunitas Pembelajaran dan Penggunaan Platform Pendidikan terhadap Kompetensi Pedagogis Guru Sekolah Dasar - Apremedian; Supandi; Nurkolis (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the effect of learning community effectiveness and the use of the Rumah Pendidikan Platform on the pedagogical competence of public elementary school teachers in Tanggungharjo District, Indonesia. A quantitative survey approach was employed, involving 137 teachers selected through proportional random sampling. Data were collected using questionnaires that had undergone validity and reliability testing and were analyzed using simple and multiple linear regression with SPSS 27. The results indicate that learning community effectiveness has a positive and significant effect on teachers’ pedagogical competence (r = 0.820; R² = 0.703), explaining 70.3% of the variance. The use of the Rumah Pendidikan Platform also demonstrates a positive and significant effect (r = 0.684; R² = 0.469), accounting for 46.9% of the variance. Simultaneously, learning community effectiveness and platform utilization significantly influence pedagogical competence (R = 0.852; R² = 0.725). These findings highlight the importance of strengthening learning communities and optimizing digital education platforms to enhance teachers’ pedagogical competence. The study recommends that education authorities prioritize integrated digital training initiatives within teacher working groups to ensure sustainable improvement in pedagogical competence.